False-Belief Understanding and Language Ability Mediate the Relationship between Emotion Comprehension and Prosocial Orientation in Preschoolers - Ornaghi, Veronica; Pepe, Alessandro; Grazzani, Ilaria (Frontiers in Psychology, 2016)
Emotion comprehension is known to be a key correlate and predictor of prosociality from early childhood. The present study look at their relation within the wide theoretical construct of social understanding which includes a number of socio-emotional skills, as well as cognitive and linguistic abilities. Theory of mind, especially false-belief understanding, has been found to have positive correlations with both emotion comprehension and prosocial orientation. Similarly, language ability is known to play a key role in children’s socio-emotional development. The combined contribution of both false-belief understanding and language in explaining the relation between emotion comprehension and prosociality has yet to be investigated. Thus, in the current study, we conducted an in-depth exploration of how preschoolers’ false-belief understanding and language ability each contribute to modeling the relationship between their comprehension of emotion and their disposition to act prosocially towards others, after controlling for age and gender. Participants were 101 4-to-6 year old children (54% boys), who were administered measures of language ability, false-belief understanding, emotion comprehension and prosocial orientation. Multiple mediation analysis of the data suggested that false-belief understanding and language ability jointly and fully mediated the effect of preschoolers’ emotion comprehension on their prosocial orientation. Analysis of covariates revealed that gender exerted no statistically significant effect, while age had a trivial positive effect. Theoretical and practical implications of the findings are discussed.